Formation of Students Communicative Competence (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Today, as you know, the idea of a competence-based approach and a list of key competencies are reflected in new State standards. The requirements of systemically organized intellectual, communicative, reflective, self-organizing principles that allow successful organization of activities in a wide professional, pedagogical and cultural contexts are gaining increasing priority.